Self-efficacy, emotional state and self-regulated learning in university students during COVID-19 pandemic - Gaeta González, Martha Leticia (2021)
The COVID-19 pandemic has had a strong impact on all areas of society, including education. At the university level, online instruction has generated several challenges for students to manage their personal resources and achieve academic goals. From a socio-cognitive perspective, this study aims to analyze the relationship between self-efficacy, emotional state, and self-regulated learning in university students and contrast its variation according to gender and academic term during COVID-19 pandemic confinement. Participants were 1665 people from different Mexican universities who answered an online questionnaire between June and August 2020. Regression analysis indicated that self-efficacy to cope with stressful situations and emotions of despair, fear, and hope, positively affect self-regulated learning, while anger does it negatively. Women indicated more significant levels of fear, gratitude, compassion, and self-regulated learning. Postgraduate students reported tranquility, hope, and gratitude with the most significant frequency. On the other hand, the undergraduate students’ group from the last semesters (7th-10th) indicated anger, fear and disinterest more frequently and the lowest level of self-efficacy and self-regulated learning, compared to students from initial and intermediate academic periods. From these data, it is necessary to promote actions that support university students in enhancing their capacities to improve their academic achievement by awareness of the difficulties that can limit their learning and careful control of their cognition, emotional state, and behavior during and after confinement.